Bioestimulante à base de extrato da alga marinha Ascophyllum nodosum e ácidos fúlvicos na tolerância do estresse salino em soja - Silva, Bruna Alves da (2023)
Soybean [Glycine max (L.) Merril] is one of the main crops in the world, of great economic interest, it is rich in amino acids and lipids, becoming an important source of vegetable protein and raw material in the production of biodiesel. Due to its plasticity, soybean cultivation is widespread worldwide, so that the crop is prone to various abiotic and biotic stresses. The main abiotic stresses are caused by changes in the environment, such as lack of water and soil salinization. Salt stress is caused by excess salts of natural and anthropogenic origin. One of the human activities that most causes salinity is the use of poor-quality water in irrigation. Currently, the process of salt accumulation in agricultural areas is increasing, mainly due to the excess of solutes in physiological processes and compromising food production. Salt stress has osmotic and ionic components, and both alter biometric aspects and the plant's metabolism. As a way to mitigate negative aspects caused by salinity, research is carried out in different modalities and with different technologies. As a result, the application of biostimulants is used to provide better conditioning of the plant to stressful conditions and improve nutrient absorption. Among the different compositions of biostimulants, hydrolyzed proteins, seaweed extracts, humic acids and nanoparticles may be present. Thus, the objective of the present work was to analyze the use of a biostimulant based on extracts of the seaweed Ascophyllum nodosum (L.) and fulvic acids on biochemical, physiological parameters and morphophysiological indices of soybeans under saline stress. For this purpose, soybean plants were subjected to saline stress with a saline solution containing the salts NaCl, CaCl2, MgCl2 in a ratio of 7:2:1 resulting in conductivity of 4.0 dS.m-1, and the second factor corresponded to the application of biostimulant at phenological stage V3 with collection of 20 plants; subsequently another 20 plants were sprayed with application of the biostimulant at the V3+R1 phenological stages and collected for biochemical and physiological analyses. The application of the biostimulant only in V3 showed that irrigation composed of saline solution did not significantly compromise the relative water content of the plant and there were activities of the antioxidant enzymes APX, CAT and SOD. Among the non-enzymatic mechanisms, proline and carotenoids also showed an increase. Despite the initial damage caused by salt stress, electrolyte leakage and MDA remained lower with the use of the biostimulant. With the application of V3+R1, the results showed that the use of the biostimulant led to greater growth of the root system, stem diameter, leaf area, number of leaves and relative growth. The effects of saline stress caused a reduction in leaf water potential and relative water content. VE and MDA were lower with the biostimulant. Stomatal conductance was higher and resulted in higher photosynthetic rates. The enzymatic antioxidant system showed an increase in the activities of APX, CAT and SOD. There was an increase in the content of proline, soluble proteins and carotenoids. Therefore, the use of the biostimulant with Ascophyllum nodosum (L.) and fulvic acids is efficient in conditioning and developing antioxidant defense mechanisms and tolerance in attenuating the deleterious effects of salt stress in soybeans.